Spatial Clustering Of Tourism Investment Potential In Tomohon City: Klasterisasi Spasial Potensi Investasi Pariwisata Kota Tomohon - Efraim R. S. Moningkey; Nelsi Timang; Kristofel Santa (Academia Open, 2026)
General Background: Tourism represents a strategic driver of regional economic development that requires spatially grounded analytical approaches to support investment planning. Specific Background: Tomohon City, a volcanic tourism area in North Sulawesi, contributes substantially to regional economic output but experiences uneven spatial distribution of tourism investment due to accessibility and infrastructural variation. Knowledge Gap: Tourism investment planning in Tomohon has not previously integrated spatial clustering analysis with interactive geovisualization to classify investment potential systematically. Aims: This study aims to analyze and visualize tourism investment potential in Tomohon City using K-Means spatial clustering integrated into a WebGIS platform. Results: Based on 500 tourism sites and indicators including accessibility, visitor volume, supporting facilities, and estimated return on investment, three clusters were identified: high potential areas covering 28% of the region with ROI of 25–35%, medium potential areas covering 52% with ROI of 15–25%, and low potential areas covering 20% with ROI of 5–15%. Novelty: This research introduces an integrated spatial model combining K-Means clustering and WebGIS visualization for tourism investment assessment in a volcanic urban setting. Implications: The results provide a replicable spatial decision-support framework for tourism investment planning aligned with sustainable development objectives. Highlights • Tourism sites are spatially grouped into three investment potential categories• Central urban areas dominate high-return tourism zones• Web-based mapping supports structured spatial decision-making Keywords Spatial Analysis; Tourism Investment; WebGIS; K-Means Clustering; Tomohon City